PEMBERDAYAAN WIRAUSAHA MUDA DESA KEDUNGREJO MELALUI PELATIHAN ARTIFICIAL INTELLIGENCE DAN STRATEGI TIKTOK AFFILIATE UNTUK MENINGKATKAN KAPASITAS DIGITAL DAN EKONOMI LOKAL - Siti Labiba Kusna; Ainu Zuhriyah; Muhammad Firdaus; Siti Imroatun Solikah; Septiani Nur Azizah; Tita Rosa Ardinda (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service program addresses the limited digital literacy and underutilization of technology in promoting local products among young entrepreneurs in Kedungrejo Village. The program aims to empower young entrepreneurs by enhancing their digital capacity and supporting local economic development through training on Artificial Intelligence (AI) and TikTok Affiliate strategies. The activity employed the Asset-Based Community Development (ABCD) approach, involving interactive training sessions, demonstrations, and hands-on practice. The results show a significant increase in participants’ understanding by 30%, along with strong motivation, as 90% of participants expressed readiness to apply the acquired skills. This program contributes to strengthening digital entrepreneurship and expanding market access for local products, thereby supporting sustainable local economic growth.